A Cross‐Shaped Monomer as Building Block for Molecular Textiles. Issue 4 (23rd March 2023) - Kroonen, Camiel C. E.; D'Addio, Adriano; Prescimone, Alessandro; Fuhr, Olaf; Fenske, Dieter; Mayor, Marcel
Abstract: The exploration of new materials is timeless. Especially 2D‐materials have gotten much interest in the last decades. This work proposes a new route towards a fascinating class of 2D materials: molecular textiles. The suggested bottom‐up approach focuses on the 2D self‐assembly of a cross‐shaped monomer at the water/air interface. A 3D cross‐shaped motive was designed, synthesized, and characterized, which exhibits the required structural features, i. e ., static and dynamic control. Analysis of the cross‐shaped motive by 1 H‐NMR spectroscopy, X‐ray structure, and chiral stationary phase HPLC proved the rigidity and stability of the system, and thus also its potential for the here suggested new strategy towards molecular textiles. Three variants of a Schiff ‐base precursor pair functionalized monomer were synthesized and characterized by 1 H‐NMR spectroscopy, 13 C‐NMR spectroscopy, and mass spectrometry. Finally, the network formation of the monomer is shown to be triggered by deprotonation of its ammonium salt, corroborated with FT‐IR analysis. Abstract :